PENGARUH EFEKTIVITAS KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP KETEPATAN PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN DI ERA PANDEMI COVID-19 DENGAN IMPLEMENTASI ERP SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2019-2020) - Faishal Irza Maulida; Aditya Septiani (Diponegoro Journal of Accounting, 2022)
The purpose of this study is to examine the impact of audit committee effectiveness and audit quality on the timeliness of financial reporting during the pandemic era with ERP implementation as a moderating variable. The independent variables used in this study are the expertise of the audit committee members, the frequency of audit committee meetings, the size of the audit committee, the tenure of the audit committee, multiple directorship of the members of the audit committee and the quality of the audit. While the dependent variable used in this study is the timeliness of financial reporting and the moderating variable in this study is the implementation of ERP.The population in this study consists of manufacturing companies affected by COVID-19 that are listed on the Indonesia Stock Exchange (IDX) for the period 2019-2020. Purposive sampling is used to as the sampling method. Out of 195 manufacturing companies, there were 140 samples that had complete financial reports for the 2019-2020 period.The results of this study indicate some characteristics of the audit committee effectiveness, such as frequency of meeting and tenure, as well as audit quality, have a significant effect on the timeliness of financial reporting when the COVID-19 pandemic occurred, while expertise, size, multiple directorship have no significant effect on the timeliness of financial reporting. ERP implementation is able to moderate the relationship that exists between meeting frequency, tenure and audit quality with the timeliness of financial reporting during the pandemic era.